Maternal intake of pesticide residues from fruits and vegetables in relation to fetal growth. (October 2018) - Chiu, Yu-Han; Williams, Paige L.; Gillman, Matthew W.; Hauser, Russ; Rifas-Shiman, Sheryl L.; Bellavia, Andrea; Fleisch, Abby F.; Oken, Emily; Chavarro, Jorge E.
Abstract: Objectives: To examine the associations of maternal intake of fruits and vegetables (FVs), considering pesticide residue levels, with fetal growth. Methods: We studied 1777 mothers (1275 white, 502 non-white) and their infants from Project Viva, a prospective pre-birth cohort (1999–2002). We categorized FVs as containing high or low pesticide residues using data from the US Department of Agriculture. We then used a food frequency questionnaire to estimate each participant's intake of high and low pesticide residue FVs in the first and second trimester. The primary outcomes were small-for-gestational-age (SGA; <10th percentile in birth-weight-for-gestational-age), large-for-gestational-age (LGA; ≥10th percentile in birth-weight-for-gestational-age) and preterm birth (gestational age <37 weeks). We also evaluated whether the associations between high pesticide residue FV intake and birth outcomes were modified by race/ethnicity. Results: 5.5% of newborns were SGA, 13.7% were LGA, and 7.3% were preterm. Intakes of high or low pesticide residue FVs, regardless of pregnancy trimester, were not associated with risks of SGA, LGA, or preterm birth. In addition, the associations of high pesticide FV intake with SGA and LGA were not modified by race/ethnicity. However, we observed heterogeneity in the relationship between first trimester high pesticide FV intake and risk of preterm birth by race/ethnicity (P value for interaction = 0.01), although this relationship did not persist after correction for multiple comparisons (Bonferroni corrected level of significance: P < 2.8 × 10 −3 ). Conclusions: There were no clear associations between high or low pesticide FV intake during pregnancy with SGA, LGA or preterm birth. Highlights: Little is known about whether intake of pesticide residues from FVs during pregnancy may have adverse effects on offspring. Neither intake of high or low pesticide residue FVs during pregnancy was associated with preterm birth or fetal growth. More studies are needed to investigate the impact of prenatal pesticide exposure on birth and later childhood outcomes.